Analisis Hubungan Profitabilitas Dengan Modal Intelektual Perusahaan (Studi Kasus Pada Perusahaan Pertambangan Sub Sektor Batubara di Bursa Efek Indonesia) - Amalia, Rizki Fitri; Annisa, Mutiara Lusiana (Universitas Muhammadiyah Palembang, 2018)
The purpose of this study is to see the relationship between profitability and corporate intellectual capital. The object of this research is the companies listed on the Indonesia Stock Exchange. This study uses purposive sampling. Profitability variable is measured by Return On Investment (ROI) and Net Profit Margin (NPM). The research results state that there is a significant influence on Return On Investment (ROI) and Net Profit Margin (NPM) on Intellectual Capital both simultaneously and partially. This shows that the higher the ability of the company to obtain profits encourages companies to tend to be more detailed in disclosing information, including information about Intellectual Capital.